COMPARISON OF THE DEPTH OF INDIGENOUS INTELLIGENCE WITH ARTIFICIAL INTELLIGENCE IN THE ENFORCEMENT OF CUSTOMARY LAW IN INDONESIA - Andra Bani Sagalane; Muchtarom, Achmad; Nasaruddin; Manyata, Bakas; Saptomo, Ade (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
This paper discusses the comparison between the depth of indigenous intelligence and artificial intelligence (AI) in resolving customary law cases, with a focus on the Cambokh Sumbai practice in the Lampung indigenous community. Customary law is understood as a flexible, dynamic, and contextual system based on moral ethos and cultural values that are alive in community practices. The research method used a descriptive qualitative approach with normative juridical methods and case studies. The findings show that traditional leaders produce decisions that are quick but still socially accurate because they understand kinship relations, moral values, and the internal social dynamics of the community. In contrast, artificial intelligence has limitations in processing cultural variables that are not digitally documented, so that its reasoning is generalist and unable to penetrate the social context. In conclusion, customary law through the practice of Cambokh Sumbai is a tangible manifestation of substantive justice and the implementation of Pancasila values in the lives of indigenous peoples in Indonesia.